2010
DOI: 10.1126/science.1189587
|View full text |Cite
|
Sign up to set email alerts
|

Global Convergence in the Temperature Sensitivity of Respiration at Ecosystem Level

Abstract: The respiratory release of carbon dioxide (CO(2)) from the land surface is a major flux in the global carbon cycle, antipodal to photosynthetic CO(2) uptake. Understanding the sensitivity of respiratory processes to temperature is central for quantifying the climate-carbon cycle feedback. We approximated the sensitivity of terrestrial ecosystem respiration to air temperature (Q(10)) across 60 FLUXNET sites with the use of a methodology that circumvents confounding effects. Contrary to previous findings, our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
391
10
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 496 publications
(459 citation statements)
references
References 36 publications
41
391
10
2
Order By: Relevance
“…On the other hand, estimates of net primary production and respiration in Earth system models assume a static response to temperature [e.g., Oleson et al, 2010], although there is evidence that plants can acclimate to higher temperatures on seasonal and interannual timescales [Kattge and Knorr, 2007;Atkin et al, 2008;Sendall et al, 2015]. This is consistent with other evidence that Earth system models may be overly pessimistic about the impact of higher temperatures on land carbon [Frank et al, 2010;Keenan et al, 2013;Mahecha et al, 2010], and studies which include temperature acclimation indicate that including the effects of acclimation would increase the terrestrial carbon in Earth system models [Arneth et al, 2012;Atkin et al, 2008;King et al, 2006]. Thus, the IAM models used to predict future land use conversion may be underestimating the threat to forests from deforestation, while Earth system models may be overestimating the threat to forests from higher temperatures.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, estimates of net primary production and respiration in Earth system models assume a static response to temperature [e.g., Oleson et al, 2010], although there is evidence that plants can acclimate to higher temperatures on seasonal and interannual timescales [Kattge and Knorr, 2007;Atkin et al, 2008;Sendall et al, 2015]. This is consistent with other evidence that Earth system models may be overly pessimistic about the impact of higher temperatures on land carbon [Frank et al, 2010;Keenan et al, 2013;Mahecha et al, 2010], and studies which include temperature acclimation indicate that including the effects of acclimation would increase the terrestrial carbon in Earth system models [Arneth et al, 2012;Atkin et al, 2008;King et al, 2006]. Thus, the IAM models used to predict future land use conversion may be underestimating the threat to forests from deforestation, while Earth system models may be overestimating the threat to forests from higher temperatures.…”
Section: Discussionsupporting
confidence: 79%
“…There was no significant relationship between E 0 and any of the mean annual satellite-derived indices related to canopy greenness, water and temperature over either growing season or whole year. The question if the temperature sensitivity of respiration varies over time and among vegetation types is still under debate (Davidson and Janssens, 2006;Mahecha et al, 2010;Chen et al, 2010;Yvon-Durocher et al, 2012;Jägermeyr et al, 2014). Although many evidences showed that E 0 varies among compounds and decomposition of labile SOM has lower temperature sensitivity than decomposition of recalcitrant SOM (Davidson and Janssens, 2006), some researches reported that temperature sensitivities of respiration are remarkably similar among ecosystems (YvonDurocher et al, 2012), and can be even considered as a constant (Mahecha et al, 2010).…”
Section: Characteristics Of the Model Parametersmentioning
confidence: 99%
“…It was reported that the substrates for plant growth respiration (R g ) (Amthor, 2000;Piao et al, 2010;Mahecha et al, 2010;Chapin et al, 2011) and rhizomicrobial respiration (R rhi ) Cheng, 2001, 2004;Dilkes et al, 2004;Heinemeyer et al, 2006Heinemeyer et al, , 2007Moyano et al, 2007Moyano et al, , 2008Gaumont-Guay et al, 2008;Kuzyakov and Gavrichkova, 2010;Mahecha et al, 2010) are both derived from current photosynthate, and their respiratory rates couple closely with GPP. During the process of plant photosynthesis, growth respiration (R g ) consumes some photosynthate to provide energy for satisfying growth demand.…”
Section: Description Of the Rersmmentioning
confidence: 99%
“…Arguably, these values are the most relevant for predicting long term changes, since uptake and respiration ultimately depend on C made available by decomposition. Why these values remained especially low and how they may change in the long term remains to be explored, but rather low sensitivities are consistent with some integrative studies at the ecosystem level (Mahecha et al, 2010 behaviour, the answer is not clear and will require further research. Ultimately, the better option may be to abandon such model and develop better validated mechanistic alternatives for prediction purposes.…”
Section: B)mentioning
confidence: 93%